Chapter Old landmarks and new functions. Coastal architectures redesign the geography of the coastal belts - Ivona, Antonietta (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
If from 2nd post-war period and for following 20 years coastal space has maintained even a minimal break with anthropized spaces, starting from the 1970s rapid industrial development has increasingly occupied coasts. These changes along costal space can be understood referring to maritime-coastal region, which are places between land and sea, profoundly different by integration of resources. The chapter focuses its attention on one of the most symbolic maritime cultural assets: lighthouses. They are distributed along the European coastlines, responding to same historical function, and evoking a common past.